Why Social Commerce Tiktok Shop Was Closed By The Indonesian Government - syafril syafril; Effiyaldi Effiyaldi; Yemima Yemima; Wahyudi Wahyudi; Selvanus Selvanus; Hidayatullah As-Syahri; Hari Susanto (Hut Publication Business and Management, 2024)
This research aims to find answers to why the Indonesian Government closed the Social Commerce Tiktok Shop. The approach in this research is descriptive qualitative using case study and literature study methods. This research aims to find answers to the problem formulation from various literary sources from books, scientific journals and other relevant news media. From the results of the research conducted, it can be seen that there are various reasons for the Indonesian government to close social commerce Tiktok shops, including violations in buying and selling activities at Tiktok shops such as predatory pricing, dumping and shadow banning which are detrimental to local MSME traders in Indonesia. It is hoped that this research will be a reference for future researchers regarding the Tiktok shop application with different variables.